Drafting in long-track speed skating team pursuit on the ice rink - van den Brandt, F. A. P.; Menting, S. G. P.; Hettinga, F. J.; Elferink-Gemser, M. T. (Journal of Sports Sciences, 2023)
Drafting is distinctive for team pursuit races in long-track speed skating. This study aims to compare the impact of drafting on physical intensity (heart rate [HR]) and perceived intensity (ratings of perceived exertion [RPE]) per drafting position. Eighteen skilled male (n = 9) and female (n = 9) skaters (20.0 ± 4.8 years) skated three trials, in first, second or third position, with consistent average velocity (F2,10 = 2.30, p = 0.15, np2 = 0.32). Differences in HR and RPE (Borg CR-10 scale) were compared within-subjects (three positions) using a repeated-measures ANOVA (p < 0.05). Compared to the first position, HR was lower in the second (benefit 3.2%) and third (benefit 4.7%) position and lower in third compared to second position (benefit 1.5%), observed in 10 skaters (F2,28 = 28.9, p < 0.001, np2= 0.67). RPE was lower when comparing second (benefit 18.5%) and third (benefit 16.8%) position to first (F1.3,22.1 = 7.02, p < 0.05, np2= 0.29) and similar for third and second positions., observed in 8 skaters. Even though the physical intensity was lower when drafting in third versus second position, the perceived intensity was equal. There were large interindividual differences between skaters. Coaches are advised to adopt a multidimensional, tailored approach when selecting and training skaters for a team pursuit.